2016
DOI: 10.26753/jikk.v12i3.164
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN OUTCOME PASIEN CEDERA KEPALA DI IGD RSUD Prof. Dr. MARGONO SOEKARDJO PURWOKERTO

Abstract: Trauma is one of the biggest causes of death in the world. Thousands of people died from trauma each years. Many trauma occur in developing countries or countries with low incomes. The survey carried out showed 90% of trauma occur in developing countries. Outcome head injury patients determined from the initial condition when the patient entered in the ER (Emergency Room). Analysis of the patient's condition will determine the appropriate nursing actions that affect patient outcome. The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
5
0
6
Order By: Relevance
“…The degree of severity appears to have a strong influence on the chances of survival and healing. In line with research conducted by Suwaryo, (Wihastuti, and Fathoni (2016) et al, 2018). It can be concluded that the lower the GCS score, the more predictable the patient is with a poor prognosis (Sharf and El-Gebali, 2013).…”
Section: Resultssupporting
confidence: 91%
“…The degree of severity appears to have a strong influence on the chances of survival and healing. In line with research conducted by Suwaryo, (Wihastuti, and Fathoni (2016) et al, 2018). It can be concluded that the lower the GCS score, the more predictable the patient is with a poor prognosis (Sharf and El-Gebali, 2013).…”
Section: Resultssupporting
confidence: 91%
“…Manajemen yang cepat dan tepat dapat menghindarkan pasien cedera kepala dari mortalitas dan morbiditas (Suwaryo, Wihastuti, & Fathoni, 2016). Seorang perawat memiliki peran penting dalam manajemen pasien cedera kepala (Varghese, Chakrabarty, & Menon, 2017).…”
Section: Pendahuluanunclassified
“…Jawa tengah merupakan terbesar ketiga dengan jumlah penduduk terbesar yang mengalami disabilitas, yaitu sebanyak 2,1 juta. Jenis penyebab disabilitas yang didapatkan yaitu karena amputasi tangan dan kaki, cacat tulang sendi, tulang punggung, folio, tuberkulosis, cerebral palsy dan paraplegia yang disebabkan karena kecelakaan atau trauma, kemudian merusak fungsi sensorik dan motorik (Kemenkes RI, 2014;Suwaryo, Wihastuti, & Fathoni, 2016).…”
Section: Jurnal Ilmiah Kesehatan Keperawatanunclassified